HOW DO STUDENTS' DECISION-MAKING ABILITY IN SOLVING OPEN-ENDED PROBLEMS? - Wasilatul Murtafiah; Nurcholif Diah Sri Lestari; Faridah Hanim Yahya; Davi Apriandi; Edy Suprapto (IKIP Siliwangi and I-MES, 2023)
An open-ended problem in learning mathematics is a problem with more than one answer or method of solving. In solving open-ended problems in learning mathematics, one of the abilities students must use is decision-making ability. Each student has a variety of capacities, so this study aims to determine students' decision-making abilities in solving open-ended problems in learning mathematics. The type of research used is descriptive qualitative research. The subjects of this study were four students with different numbers of correct answers in working on open-ended problems. Data collection was carried out using tests and interviews. The results showed that (1) the decision-making ability of the subject who answers correctly for both problems is complete because they fulfill all indicators, the subject can identify goals, make decisions, evaluate the results of determination, and present and remember between problems with things known to the problem and related to decisions that have been taken correctly; (2) decision-making ability for subjects with wrong answers on one number or two numbers is incomplete because they only fulfilled two indicators, the subject can identify goals, make decisions, is less able to evaluate decision results and present and remember between problems with things known to the problem, and related to decisions that have been taken with correct. Mathematics teachers should often reinforce students to practice operating integers because it is a prerequisite for learning mathematics at the middle and high school levels.